Organizational Financial Performance in the Context of Sustainability: A Form of Transparency in the Financial Performance of Business Entities - Abdul Fatah Hassanudin (Outline Publisher, 2025)
Financial performance reporting in the context of sustainability has become increasingly important in recent years. This study aims to analyze the role of financial perfomance evaluation in the context of business sustainability. The results show that financial performance evaluation not only assesses current operational effectiveness but also serves as a predictor of business sustainability in the future. In the context of business sustainability, financial performance evaluation not only measures financial output but also efficient resource management. An Inclusive and comprehensive approach is needed to connect these two aspects. This reaseach is expected to provide guidance for business practitioner and polcymakers in formulating sustainability strategies that are integrated with their financial performance evaluation.